2014
DOI: 10.4174/astr.2014.87.5.245
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of monitored anesthesia care with dexmedetomidine and spinal anesthesia during varicose vein surgery

Abstract: PurposeThe purpose of this study was to investigate the effectiveness and safety of monitored anesthesia care (MAC) using dexmedetomidine for its sedative and analgesic effect during varicose vein surgery.MethodsForty-two patients, who underwent varicose vein surgery, were divided into the MAC group (n = 20) or the spinal anesthesia group (n = 22) for randomized clinical trial. In the MAC group, dexmedetomidine was administered by a loading dose of 1 µg/kg for 10 minutes, followed by a maintenance infusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Great or small saphenous vein stripping is a commonly performed surgical procedure as a treatment for varicose veins of the lower extremity. There are several anesthetic methods, including general anesthesia, neuraxial block, and peripheral nerve blocks, such as femoral nerve block, popliteal nerve block, and posterior cutaneous nerve block [ 1 2 3 4 ]. Monitored anesthesia care (MAC) with local anesthesia is another option for patients undergoing vein stripping.…”
Section: Introductionmentioning
confidence: 99%
“…Great or small saphenous vein stripping is a commonly performed surgical procedure as a treatment for varicose veins of the lower extremity. There are several anesthetic methods, including general anesthesia, neuraxial block, and peripheral nerve blocks, such as femoral nerve block, popliteal nerve block, and posterior cutaneous nerve block [ 1 2 3 4 ]. Monitored anesthesia care (MAC) with local anesthesia is another option for patients undergoing vein stripping.…”
Section: Introductionmentioning
confidence: 99%
“…Eun-Jin Moon et al 14 compared monitored anaestesia care (MAC) with dexmedetomidine (1 µg/kg) and intermittent ketamine with spinal anaesthesia(SA) for patient satisfaction using ISAS scale{Iowa satisfaction with anaesthesia scale. The verbal rating scale 0(worst) to 10(best)} and concluded that patient's(p=0.018) and surgeon's satisfaction(p=0.001) were lower in MAC group (7.4 and 6.2 respectively) compared to SA group (9.0 and 9.1 respectively).…”
Section: Prerana Shah Et Almentioning
confidence: 99%